Prevalence and associated factors of sarcopenia risk and possible sarcopenia among older homeless adults in a home for destitute, Thailand: A cross-sectional study - Whaikid, Phatcharaphon; Piaseu, Noppawan; Tantiprasoplap, Sukanya; Krongthaeo, Suphanna; Srisuk, Wasana; Jitwiriyatham, Theeraphorn; Tantipongsirikul, Jirapa; Subtema, Chanokporn (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Sarcopenia threatens the functional ability of older adults and may be underdiagnosed in homeless populations. Older homeless adults face heightened risks due to malnutrition and comorbidities. However, evidence on sarcopenia in this group remains limited, particularly in institutional settings in Thailand. Understanding the prevalence and associated factors of sarcopenia in this vulnerable population is essential to guide early detection, tailored interventions, and policy development. Objectives: To investigate the prevalence of sarcopenia risk and possible sarcopenia, and to identify associated risk factors among older homeless adults. Methods: This cross-sectional study was conducted in 2023 among homeless adults aged 50 years or older residing in a home for the destitute. Participants were purposively recruited based on predetermined inclusion criteria. Sarcopenia risk and possible sarcopenia were determined according to the Asian Working Group for Sarcopenia (AWGS) 2019 guidelines. Calf circumference was measured to identify sarcopenia risk, while handgrip strength and physical performance assessed using the Five-Times Sit-to-Stand Test were used to determine possible sarcopenia. Data were analyzed using descriptive statistics and multinomial logistic regression. Results: Of the 163 participants, 74.9% were classified as having sarcopenia risk, while 71.2% had possible sarcopenia. Multinomial logistic regression analysis revealed that a low body mass index (BMI) was significantly associated with sarcopenia risk (OR = 0.538, 95% CI [0.359, 0.807], p = 0.003). Possible sarcopenia was significantly associated with older age (OR = 1.173, 95% CI [1.061, 1.298], p = 0.002), lower BMI (OR = 0.564, 95% CI [0.448, 0.710], p < 0.001), and the presence of comorbidities (OR = 5.045, 95% CI [1.025, 24.847], p = 0.047). Conclusion: Sarcopenia risk and possible sarcopenia are highly prevalent among older homeless adults. BMI was a key protective factor, while age and comorbidities significantly increased the risk. These findings highlight the need for targeted interventions focusing on nutrition and early prevention strategies to mitigate sarcopenia in this vulnerable population. Nurses play a critical role in early screening and implementing tailored interventions to support prevention and management efforts.